Hubungan antara pegangan nilai moral dengan media massa: Tinjauan ke atas remaja Melayu luar bandar - Ab. Halim Tamuri; Zarin Ismail (Universiti Kebangsaan Malaysia, 2009)
The influx of negative contents in the mass media, both local and abroad, has created menace to Malay Muslim youths today. Due to the fast development of modern technology, it is considered one of the most influential factors with great impact on the youths, both in urban and rural areas. This paper is to discuss a study on the influence of mass media on a group of Malay students in Sabak Bernam, Selangor. The objectives of the study are to ascertain the level of exposure of the youths to the different types and contents of the mass media and analyze the relationship between the influence of mass media and the internalization of their ethical values by using a set of questionnaires on 398 Form 4 Malay students from the district